2018
DOI: 10.1155/2018/4320195
|View full text |Cite|
|
Sign up to set email alerts
|

The Epidemiology of Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in China

Abstract: Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) are life-threatening disease. However, there are only few epidemiologic studies of SJS/TEN from China. To analyze the clinical characteristics, causality, and outcome of treatment for SJS/TEN in China, we reviewed case reports of patients with SJS/TEN from the China National Knowledge Infrastructure (CNKI) and Wanfang database from 2006 to 2016 and patients with SJS/TEN who were admitted to the First Affiliated Hospital of Fujian Medical Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
35
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 69 publications
(51 reference statements)
2
35
1
9
Order By: Relevance
“…Our finding was in accordance with results from China or South‐East Asian countries in which carbamazepine, allopurinol and antibiotics were the most commonly implicated drugs to cause SJS/TEN . However, among antibiotic‐induced SJS/TEN, the third‐generation cephalosporins were the most reported in our study instead of penicillins as the predominant group in those studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our finding was in accordance with results from China or South‐East Asian countries in which carbamazepine, allopurinol and antibiotics were the most commonly implicated drugs to cause SJS/TEN . However, among antibiotic‐induced SJS/TEN, the third‐generation cephalosporins were the most reported in our study instead of penicillins as the predominant group in those studies.…”
Section: Discussionsupporting
confidence: 92%
“…22 Our finding was in accordance with results from China or South-East Asian countries in which carbamazepine, allopurinol and antibiotics were the most commonly implicated drugs to cause SJS/ TEN. 27,42 However, among antibiotic-induced SJS/TEN, the thirdgeneration cephalosporins were the most reported in our study instead of penicillins as the predominant group in those studies. In fact, the tendency of overuse of antibiotics in Vietnam, especially third-generation cephalosporins, is an important health issue in the country and greatly influences the structure of drug-induced MLOSCAR.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…16 Another study reviewed case reports of patients with SJS/TEN from 2006 to 2016 and found 94/166 cases of TEN, 29.5% of which were caused by antibiotics. 17 No current consensus exists on how this disease should be treated. There are only health care protocols established by local hospitals.…”
Section: Discussionmentioning
confidence: 99%